Open-cell copper foam joining: joint strength and interfacial behaviour - Zahri, Nur Amirah Mohd; Yusof, Farazila; Ariga, Tadashi; Haseeb, A.S. Md. Abdul; Mansoor, Muhammad Adil; Sukiman, Nazatul Liana (Taylor & Francis, 2019)
A copper (Cu) foam was brazed with Cu-4.0Sn-9.9Ni-7.8P filler foil for joint strength and interface analysis. Brazed 50 pores per inch (PPI) Cu foam yielded a maximum compressive strength of 14.4 MPa with a 127% increment compared to nonbrazed Cu foam. 15 PPI Cu foam produced a maximum shear strength of 2.7 MPa. Scanning electron microscopy showed that the thickness of the brazed seam decreased with increasing the Cu foam’s PPI. The formation of the Cu, Cu3P (P: phosphorus) and Ni3P (Ni: nickel) at the Cu/Cu foam interface was validated using energy-dispersive X-ray spectroscopy (EDX) and X-ray diffraction. EDX line scanning analysis revealed the diffusion of P and Ni into Cu foam, which took place via capillary force action. © 2019, © 2019 Institute of Materials, Minerals and Mining.